202 Pupillary Changes After Nonconcussive High-Acceleration Head Impacts in High-School Football Athletes. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Joseph, Jacob R; Swallow, Jennylee S; Willsey, Kylene; Lapointe, Andrew P; O'Connor, Kathryn; Szerlip, Nicholas J; Broglio, Steven P
Abstract: INTRODUCTION: Previous studies have shown that nonconcussive high-acceleration head impacts (HHI) may be associated with neuronal and axonal injury. The pupillary light reflex is a potential objective, noninvasive measure that may be able to assess these changes. This study investigates the effect of HHI on pupillary metrics, as measured by a pupillometer, even in the absence of a diagnosed concussion. METHODS: A prospective observational cohort study involving high-school football athletes (n = 18) was performed. Athletes were monitored for head impact frequency and magnitude over a season using the Head Impact Telemetry System. Pupillary assessments were performed at baseline, midseason, after HHI (defined as exceeding 95 g linear acceleration and 3760 rad/s2 rotational acceleration), and end of season using the NeurOptics NPi-200 pupillometer. The Sport Concussion Assessment Tool 5th Edition (SCAT5) was also performed at each time point. Comparisons between time points were calculated using a repeated measures ANOVA and a t -test. RESULTS: Seven athletes sustained HHI without a related diagnosed concussion. Following HHI, these athletes had decreased dilation velocity (mean difference = 0.139; P  = .048), percent change in pupil diameter (mean difference = 3.643; P  = .002), and maximum constriction velocity (mean difference = 0.744; P  = .010) compared to a same athlete midseason evaluation. No significant changes occurred between SCAT5 scores at midseason and high impact, although effect sizes reached d = .65. CONCLUSION: Measurable changes in pupil response were demonstrated following HHI. These results suggest that nonconcussive HHIs may affect intrinsic brain reflex pathways.